Treatment technologies for petroleum refinery effluents: a review - Diya'uddeen, B.H.; Daud, Wan Mohd Ashri Wan; Abdul Raman, Abdul Aziz (2011)
This paper presents a brief account of different technologies used for the treatment of petroleum refinery effluents (PRE). Broadly, PRE treatment is accomplished in two stages, namely, a series of pre-treatment steps, in which suspended matter, oil and grease are reduced, and an advanced stage, in which wastewater contaminants are decreased to certain acceptable discharge limits. Photocatalytic degradation techniques have been widely used in water and wastewater treatment. However, the literature regarding PRE treatment is scarce, and the technique is still not being utilised on an industrial scale in refineries. This is largely due to limited research findings discussing PRE treatments. Most researches are focused on treating singular contaminants found in PRE, e.g., phenols, sulphides, oil, grease and other organic components. This review focused on works that investigated PRE treatment by monitoring general refinery wastewater parameters, namely, chemical oxygen demand (COD), biological oxygen demand (BOD), total petroleum hydrocarbon (TPH), oil and grease (O&G), sulphate and phenols at the advanced treatment steps. This paper presents an overview of photocatalytic degradation and discusses published works with the goal of presenting the technique as an attractive and viable process unit. If optimised, this process has great potential for replacing other separation and degradation treatment approaches employed at the advanced treatment stage for PRE. Â© 2010 The Institution of Chemical Engineers.